The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.33448/rsd-v10i8.17233
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration, characterization and color stability of an isotonic beverage based on whey permeate with carotenoid powder from pequi

Abstract: The aim of our research was to elaborate, characterize and evaluate the stability under light/darkness and different temperatures (4 and 25 ºC) of the color of an isotonic beverage based on whey permeate with carotenoid extract powder from pequi, and verify its microbiological safety and sensory acceptance. The 3% (w/v) concentration of powdered carotenoid from pequi was chosen because it has osmolality (314.89 mOsmol/L) in the range of hydroelectrolytic beverages and light-yellow tint. The beverage was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, the pH values of the prepared isotonic drinks are in the same range of pH values evaluated in six commercial isotonic drinks, ranging from 2.58 to 3.75 [35]. Ferreira et al [4] found a pH value of 3.66 in an elaborated isotonic drink based on whey permeate with carotenoid powder from pequi. Gironés-Vilaplana et al [36] also evaluated the pH of different prepared isotonic drinks enriched with lemon and berries and found lower pH values that were between 2.35 and 2.88 at the beginning and between 2.46 and 2.97 at the end of the storage period.…”
Section: Physicochemical Characteristicsmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the pH values of the prepared isotonic drinks are in the same range of pH values evaluated in six commercial isotonic drinks, ranging from 2.58 to 3.75 [35]. Ferreira et al [4] found a pH value of 3.66 in an elaborated isotonic drink based on whey permeate with carotenoid powder from pequi. Gironés-Vilaplana et al [36] also evaluated the pH of different prepared isotonic drinks enriched with lemon and berries and found lower pH values that were between 2.35 and 2.88 at the beginning and between 2.46 and 2.97 at the end of the storage period.…”
Section: Physicochemical Characteristicsmentioning
confidence: 77%
“…In general, they contain water, carbohydrates in the form of monosaccharides or polysaccharides, electrolyte salts, juices, vitamins, colorants, and flavorings to improve organoleptic properties and have osmolality values close to blood osmotic pressure (270-330 mOsm per kg of water) to ensure rapid absorption and maintain hydration [3]. In sports drinks, sodium and potassium are important for replacing the electrolytes of athletes and helping them be absorbed more quickly during training without causing gastrointestinal problems [4]. In addition, the intake of carbohydrates is necessary as a source of energy in isotonic drinks [5] to offset the loss of carbohydrate stores and improve performance during exercises [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have completed sensory testing on a variety of electrolyte/sports beverages formulations containing permeates. These beverages are generally made from a combination of water, permeate, and some sort of flavoring or fruit juice/extract, for example, orange flavoring (Olson, 2003), pineapple or passion fruit flavoring (Ferreira et al, 2021), and jabuticaba berry and red fruit flavoring (Ferreira et al, 2020). In a study by Beucler et al (2005), the authors investigated the substitution of water with WP at varying levels (0%, 25%, 50%, 75%, and 100%) in a "thirst-quenching" fruit-flavored, noncarbonated, sports beverage formulation.…”
Section: Electrolyte Beveragesmentioning
confidence: 99%
“…In recent years, research has reported on the importance of the pequi in relation to antioxidant capacity, attributed mainly to pulp, due to its composition rich in compounds with antioxidant properties (Ferreira et al, 2021a;Ferreira et al, 2021b;Nascimento, Alves, Silva, & Naves, 2017;Pinheiro et al, 2018;Ribeiro, Fernandes, Alves, Margareth, & Naves, 2014).…”
Section: Introductionmentioning
confidence: 99%